Pengaruh Perawatan Tali Pusat Metode Topikal ASI dan Kasa Kering Terhadap Waktu Pelepasan Tali Pusat Bayi Baru Lahir Persalinan Post SC - Elvi Era Liesmayani; Lisya Octaviana; Erni Naibaho (Jurnal Bidan Mandiri, 2023)
Umbilical cord care aims to prevent infection and accelerate the release of the umbilical cord from the baby's stomach. Aim; Knowing the effect of umbilical cord care on the time of release of the umbilical cord with the topical breastfeeding method and cord care with the dry gauze method at Delima General Hospital. Method; The type of research used was "Pre-Experiment" and research design/"static group comparison group". The sampling technique in this study is Accidental Sampling. The number of samples in this study were 30 respondents..Results; Bivariate analysis found that there was an effect of umbilical cord care using topical breast milk and dry gauze on the time of cord extraction, with a value of p = 0.000 <0.05, then Ho was rejected, and when viewed from the t value it was 4.430 while the t table was -2.000 so it was 4.430 > 2,000 (t count > t table) thus Ho is rejected, meaning that there is a significant effect between cord care using topical ASI and dry gauze methods with the time the umbilical cord was removed. Conclusion; There was an effect of umbilical cord care using topical breastfeeding and dry gauze on the time of post-neonatal cord extraction at Delima General Hospital in Medan in 2018. Suggestions for future researchers to develop research with wider variables.